Analysis of the Impact of Stopping Study Tour, Digitalization of Learning, and Alternative Educational Tourism on Student Tourist Interest in West Java - Setiawati, Rahmi; Yuliawati, Refiana; Bunyamin, Ilham Akbar (Westscience Press, 2025)
This study aims to analyze the impact of study tour cancellations, the digitalization of learning, and alternative educational tourism on student interest in tourism in West Java. A total of 210 students participated in the study, and data were collected using a Likert scale (1-5). The research employs Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) for data analysis to assess the relationships between the constructs. The results indicate that alternative educational tourism has the strongest positive influence on student tourist interest, followed by the digitalization of learning. While the cancellation of study tours also positively affects student interest, its impact is less pronounced compared to the other two factors. The model demonstrates strong explanatory power with an R² value of 0.777 and predictive relevance with a Q² value of 0.771. These findings suggest that alternative tourism experiences and digital learning platforms play a critical role in shaping student interest in tourism, emphasizing the importance of adapting tourism education to current trends in the digital era.